"CLASSIC NMR": An In‐Situ NMR Strategy for Mapping the Time‐Evolution of Crystallization Processes by Combined Liquid‐State and Solid‐State Measurements1. Issue 34 (7th July 2014) - Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.
Abstract A new in‐situ NMR strategy (termed CLASSIC NMR) for mapping the evolution of crystallization processes is reported, involving simultaneous measurement of both liquid‐state and solid‐state NMR spectra as a function of time. This combined strategy allows complementary information to be obtained on the evolution of both the solid and liquid phases during the crystallization process. In particular, as crystallization proceeds (monitored by solid‐state NMR), the solution state becomes more dilute, leading to changes in solution‐state speciation and the modes of molecular aggregation in solution, which are monitored by liquid‐state NMR. The CLASSIC NMR experiment is applied here to yield new insights into the crystallization of m‐aminobenzoic acid.